The Inhibition of Phosphoinositide-3 Kinases Induce Resolution of Inflammation in a Gout Model - Izabela Galvão; Celso Martins Queiroz-Junior; Vivian Louise Soares de Oliveira; Vanessa Pinho; Emilio Hirsch; Mauro Martins Teixeira (Frontiers Media S.A., 2019)
Phosphoinositide-3 kinases (PI3Ks) are central signaling enzymes that are involved in many aspects of immune cell function. PI3Kγ and PI3Kδ are the major isoforms expressed in leukocytes. The role of PI3K isoforms in the resolution of inflammation is still poorly understood. Here, we investigated the contribution of PI3Kγ and PI3Kδ to the resolution of inflammation in a model of gout in mice.Methods and Results: Experiments were performed in wild-type male C57/Bl6 mice. Selective inhibitors of PI3K-γ (AS605240) or PI3Kδ (GSK045) were injected in the joint 12 h after injection of MSU crystals, hence at the peak of inflammation. Inhibition of either PI3K isoform decreased number of neutrophils that migrated in response to the injection of MSU crystals. This was associated with reduction of myeloperoxidase activity and IL-1β levels in periarticular tissues and reduction of histological score. Joint dysfunction, as seen by reduced mechanical hypernociception, was improved by treatment with either inhibitor. The decrease in neutrophil numbers was associated with enhanced apoptosis and efferocytosis of these cells. There was shortening of resolution intervals, suggesting inhibition of either isoform induced the resolution of neutrophilic inflammation. Blockade of PI3Kγ or PI3Kδ reduced Nuclear Factor kappa B (NF-κB) activation. A pan-PI3K inhibitor (CL27c) reduced inflammation induced by MSU crystals by a magnitude that was similar to that attained by the PI3Kγ or PI3Kδ selective inhibitors alone.Conclusion: Taken together, these results suggest that neutrophils can use PI3Kγ or PI3Kδ to remain in the cavity and blockade of either isoenzyme is sufficient to induce their apoptosis and resolve inflammation in a murine model of gout.